Pengaruh Stres Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Bagian SDM di PT PLN Indonesia Power UBP Suralaya Kota Cilegon-Banten - Afriyanti, Mutiara; Khaeruman, Khaeruman; Abduh, Edi Muhammad (BISMA : Business and Management Journal, 2024)
Employee performance is one of the most important parts to achieve company goals. This study aims to determine the influence of Work Stress and Work Discipline on Employee Performance in the HR department at PT. PLN Indonesia Power UBP Suralaya Cilegon-Banten City, both partially and simultaneously. The research method used is an associative quantitative method with a saturated sampling technique, involving a population and a sample of 93 employees in the HR department. The data was analyzed using SPSS Version 26. The results showed that Work Stress had a significant influence on employee performance (H1) with a significance value of 0.002 < 0.05 and calculated > ttable (3,271 > 1,987).  Work discipline also had a significant effect on employee performance (H2) with a significance value of 0.002 < 0.05 and calculated > ttable (3,274 > 1,987). Simultaneously, Work Stress and Work Discipline had a positive and significant effect on employee performance (H3) with a significance value of 0.000 < 0.05 and Fcal > Ftabel (8,734 > 3,089). The conclusion of this study is that Work Stress and Work Discipline have a significant influence on employee performance in the HR department at PT. PLN Indonesia Power UBP Suralaya Cilegon-Banten City, both individually and together.